Trace elements and stable isotopes in penguin chicks and eggs: A baseline for monitoring the Ross Sea MPA and trophic transfer studies. (September 2021) - Calizza, Edoardo; Signa, Geraldina; Rossi, Loreto; Vizzini, Salvatrice; Careddu, Giulio; Tramati, Cecilia Doriana; Caputi, Simona Sporta; Mazzola, Antonio; Costantini, Maria Letizia
Abstract: Multi-tissue trace elements (TEs), C, N concentrations and stable isotopes (δ 13 C, δ 15 N) of chick carcasses and eggs of Adélie and Emperor penguins were studied to i) provide reference data before the recent institution of the Ross Sea Marine Protected Area (Antarctica), and ii) provide conversion factors that allow estimating C, N, δ 13 C and δ 15 N in edible tissues from non-edible ones, thus improving the use of stable isotopes in contamination and trophic transfer studies. Higher concentrations of As, Cd, Cr, Cu, Hg, Mn and Pb were found in chick carcasses than in eggs, suggesting increasing contamination in recent decades and high toxicity risks for penguin consumers. Isotopic conversion factors highlighted small differences among body tissues and conspecifics. These values suggest that chick carcasses are reliable indicators of the energy pathways underlying the two penguin species, their trophic position in the food web and their exposure to TEs. Highlights: Trace element level in penguin eggs and chick tissues was higher than in past studies. Opportunistic penguin predators and scavenger may be exposed to high toxicity risks. Low vs. high C and N isotopic variability was found among chick tissues and egg parts. We provided isotopic and elemental conversion factors between tissues and egg parts.